Biomarcadores de progressão tumoral em carcinoma epidermóide da cavidade bucal - Damasceno, Thabata Coeli Dias (2017)
Currently, it is necessary to implement specific and individualized therapeutic approaches for patients with squamous cell carcinoma (EC) of the oral cavity, and the construction of biomarkers panels of tumor progression and prognosis. Neoplastic cells have a certain autonomy regarding their activation, which leads to the overexpression of cyclin D1 and reduction of the duration time of the G1 phase, leading to the increase of tumor proliferation. This work aimed to analyze the expression of cyclin D1 in EC of the oral cavity and its applicability as a biomarker of tumor progression and prognosis. A longitudinal analytical study was carried out with the inclusion of biological samples, clinical data and follow-up of 115 patients with EC of the oral cavity. The hematoxylin and eosin stained histological blades were analyzed for tumor gradient, tumor lymphocyte infiltrate pattern, tumor invasion pattern, vascular, lymphatic and perineural invasion. Validation of tissue microarray slides (TMA) and analysis of nuclear expression of cyclin D1 in EC tumor cells of the oral cavity (front and medial portion), dysplasia and epithelium adjacent to the tumor were performed by assessing the lamina Of TMA stained by the immunohistochemistry technique was categorized as high (> 140) and low (≤ 140). For the associations between the studied variables, Fisher's Chi-Square and Exact test were used, being considered significant values of p ≤ 0.05. The survival curves were calculated using the Kaplan-Meier model with a confidence index equal to 95% adjusted by the Cox multivariate regression model, with p ≤ 0, 2 (SG) and p ≤ 0.1 (SLD). Our results showed a correlation between the high TIL count and the variables T1 / T2 primary tumor size (p = 0.001) and initial staging I / II (p = 0.005); The lower TIL count was associated with smoking (p = 0.026). Tumor invasion pattern of type IV showed association with T3 / T4 tumors (p = 0.006) and stages II / IV (p = 0.028). Perineural invasion showed correlation with T1 / T2 tumors (p = 0.035). The tumor surface showed high expression of cyclin D1 in 49% of the cases, but no significance was observed with the variables analyzed. SG reduction was related to tumor size (p = 0.000) and lymph node involvement (p = 0.001) and were confirmed by multivariate analysis (p = 0.004, p = 0.066). The SLD showed association with the alcoholic habit (p = 0.048), a fact evidenced by multivariate analysis (p = 0.078), in which non-alcoholic individuals relapsed in a shorter time. It was concluded from the study that the expression of cyclin D1 did not prove to be a good marker of tumor progression and prognosis. Since its expression is more associated with the onset of tumorigenesis, and the greater occurrence of advanced clinical staging in this study would explain the lack of correlation between the expression of the protein and the clinical-pathological characteristics.